Symbiogenesis a new principle of evolution - Kozo-Poli͡anskiĭ, Boris Mikhaĭlovich, 1890-1957 (Harvard University Press, 2010)
More than eighty years ago, before we knew much about the structure of cells, Russian botanist Boris Kozo-Polyansky brilliantly outlined the concept of symbiogenesis, the symbiotic origin of cells with nuclei. It was a half-century later, only when experimental approaches that Kozo-Polyansky lacked were applied to his hypotheses, that scientists began to accept his view that symbiogenesis could be united with Darwin's concept of natural selection to explain the evolution of life. After decades of neglect, ridicule, and intellectual abuse, Kozo-Polyansky's ideas are now endorsed by virtually all biologists. Kozo-Polyansky's seminal work is presented here for the first time in an outstanding annotated translation, updated with commentaries, references, and modern micrographs of symbiotic phenomena.